The Clinton tapes : wrestling history with the president - Branch, Taylor, 1947- 1947- (Simon & Schuster, 2009)
While still a sitting president, Bill Clinton initiated a project to preserve for historians an unfiltered record of presidential experience. Clinton talks intimately over seven years to his long-time friend, a Pulitzer Prize-winning historian, about what it's like to be president, highlighting major events from Clinton's two terms, including war in Bosnia, the antideficit crusade, health reform failure, antterrorist strikes, peace initiatives, the 1996 re-election campaign, and Whitewater investigations culminating in his 1999 impeachment trial.--Publisher description